2013
DOI: 10.1097/pcc.0b013e31829f5c09
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Renal Replacement Therapy With an Automated Monitor Is Superior to a Free-Flow System During Extracorporeal Life Support*

Abstract: While free-flow ultrafiltration has the advantages of simplicity and low cost, integrated renal replacement therapy provides more accurate fluid management during extracorporeal life support. Better fluid status management with integrated renal replacement therapy may contribute to shorter duration of extracorporeal life support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 12 publications
0
19
0
1
Order By: Relevance
“…Thirty-one citations were obtained in full text and 12 of these were excluded: four investigated patients who underwent ECMO plus CRRT, but without comparison, one with ECMO plus intermittent RRT, two with duplicate publication, one with commentary, one cross-sectional survey, one with CRRT only, one with ECMO only and one review. In total, 19 studies were included, consisting of seven cohort studies [ 13 - 19 ], six case control studies [ 20 - 25 ], one historically controlled trial [ 26 ] and five studies of technical aspects [ 27 - 31 ]. Seventeen studies were published in English [ 13 - 23 , 26 ] and two in Chinese with English abstracts [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty-one citations were obtained in full text and 12 of these were excluded: four investigated patients who underwent ECMO plus CRRT, but without comparison, one with ECMO plus intermittent RRT, two with duplicate publication, one with commentary, one cross-sectional survey, one with CRRT only, one with ECMO only and one review. In total, 19 studies were included, consisting of seven cohort studies [ 13 - 19 ], six case control studies [ 20 - 25 ], one historically controlled trial [ 26 ] and five studies of technical aspects [ 27 - 31 ]. Seventeen studies were published in English [ 13 - 23 , 26 ] and two in Chinese with English abstracts [ 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Symons et al . reported that introduction of a CRRT device into the ECMO circuit provides more accurate fluid management during ECMO [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Symons observó que estos pacientes tenían un manejo más preciso de fluidos 23 , lo cual concuerda con los hallazgos de Chen, quien reportó que los sobrevivientes post-ECMO en TRRC tenían un mejor balance de líquidos 15 . Durante la combinación de ECMO y TRRC, las alarmas de presión se pueden activar en las líneas de entrada y salida de la máquina de TRRC.…”
Section: A Través Del Acoplamiento De Una Máquina De Trrcunclassified
“…As suggested by the name, CRRT allows for slow and continual removal of solutes and fluid from the extracellular space, avoiding abrupt changes in extracellular space volume and solute concentrations, which may be poorly tolerated by critically ill neonates. Further, fluid management is very efficient during CRRT and can be more precisely controlled than with fluid restriction, peritoneal dialysis, or diuretic therapy, particularly when integrated systems are used . Diffusive clearance, convective clearance, or a combination of both can be provided by CRRT, depending upon the mode utilized.…”
Section: Complications and Concurrent Therapiesmentioning
confidence: 99%
“…Further, fluid management is very efficient during CRRT and can be more precisely controlled than with fluid restriction, peritoneal dialysis, or diuretic therapy, particularly when integrated systems are used. 37 Diffusive clearance, convective clearance, or a combination of both can be provided by CRRT, depending upon the mode utilized. The efficiency of diffusive and convective clearance is related to molecular size and weight of the given molecule as well as the magnitude of the concentration gradient.…”
Section: Complications and Concurrent Therapiesmentioning
confidence: 99%